The Concept of Religion: Its Essence, Functions, and Role in Human Life - Anisa Nuraeni; Bintang Outra Cakti; Nurjaya Nurjaya; Hudallah Hudallah; Rosidin Rosidin (Penerbit Hellow Pustaka, 2025)
This study aims to examine the concept of religion, focusing on its essence, functions, and integral role in human life since prehistoric times. Religion has been an inseparable part of civilization, significantly influencing both individuals and societies. Utilizing a qualitative approach, this study analyzes diverse religious perspectives and their implications for individual formation and social dynamics. Data were collected through a comprehensive literature review across various academic disciplines. The main findings reveal that religion plays a vital role in providing spiritual guidance, instilling moral values, and fostering social cohesion. It also serves as a crucial framework for individuals to understand the meaning of life and the purpose of existence. The implications of this research are relevant; the discussion highlights how religious beliefs significantly shape personal identity, influence ethical behavior, and regulate communal interactions. A deep understanding of the functions and roles of religion can contribute to constructive interfaith dialogue, promote tolerance, and harness the positive potential of religion to address contemporary social challenges. The originality of this research lies in its holistic and integrated analysis of the concept of religion. This study comprehensively integrates the essential and functional dimensions, as well as the role of religion in human life, providing a new framework for understanding the relevance and dynamics of religion in modern society.